Penggunaan OAINS sebagai Faktor Risiko Dispepsia - Wahidah, Putri Kamila; Wardani, Dyah Wulan Sumekar Rengganis; Iyos, Rekha Nova (Medula, 2025)
Dyspepsia is a syndrome characterized by a collection of symptoms such as epigastric discomfort, burning sensation, nausea, vomiting, bloating and satiety. These symptoms can be chronic and recur frequently, requiring long-term therapy. If left untreated, dyspepsia can interfere with daily activities and increase medical costs. In Indonesia, the prevalence of dyspepsia is increasing significantly, with major risk factors including irregular diet, alcohol consumption, stress, and the use of non-steroidal anti-inflammatory drugs (NSAIDs). Long-term use of NSAIDs can damage the gastric mucosa, increase gastric acid production, and cause gastrointestinal complications such as peptic ulcers and gastrointestinal bleeding. The main mechanism of NSAID side effects involves inhibition of the COX-1 enzyme which reduces the production of protective prostaglandins in the gastric mucosa. In addition, some patients with a history of gastric disease are more susceptible to side effects due to NSAIDs. Therefore, preventive strategies such as the use of selective COX-2 inhibitors and the combination of NSAIDs with proton pump inhibitors (PPIs) are effective approaches in reducing the risk of dyspepsia and related complications. The impact of dyspepsia is not only physical but also affects mental, social and emotional aspects. Sleep disturbances and anxiety are common in people with chronic dyspepsia, which can reduce productivity and quality of life.